Clinical efficacy of protein-bound polysaccharide K in patients with gastric cancer undergoing chemotherapy with an oral fluoropyrimidine (S-1). Issue 6 (June 2015) - Namikawa, T.; Fukudome, I.; Ogawa, M.; Munekage, E.; Munekage, M.; Shiga, M.; Maeda, H.; Kitagawa, H.; Kobayashi, M.; Hanazaki, K.
Abstract Background The aim of the present study was to evaluate the clinical significance of protein-bound polysaccharide K (PSK) in patients with primary gastric cancer who were being treated with an oral fluoropyrimidine (S-1). Methods Clinical reports of 190 gastric cancer patients treated with S-1 chemotherapy, with or without PSK, at Kochi Medical School between 2007 and 2012 were investigated retrospectively to analyze survival. The neutrophil:lymphocyte ratio (NLR) was also evaluated as indicator of the immunoenhancing effect of PSK. Results Overall survival was significantly longer in patients treated with S-1 + PSK than in those given S-1 alone (hazard ratio for death, 0.608; 95% confidence interval 0.375–0.985; P = 0.041). Furthermore, there was a tendency for changes in the NLR during chemotherapy to be lower in the S-1 + PSK group than in the S-1 group, but the difference did not reach statistical significance (P = 0.054). When patients were divided into groups based on preoperative NLR (i.e. <2.5 and ≥2.5), the mean (±SEM) NLR 1 month after the beginning of chemotherapy in the NLR ≥2.5 subgroup was significantly lower in patients treated with S-1 + PSK rather than S-1 alone (1.7 ± 0.7 vs. 3.3 ± 4.1, respectively; P = 0.043). Conclusions Immunochemotherapy using PSK improves the survival of patients with advanced gastric cancer. The NLR may be a useful biomarker for evaluating prognosis in these patients.